The threat of social decline: income inequality and radical right support - Engler, S; Weisstanner, D (Routledge, 2020)
Income inequality and radical right parties have both been on the rise in Western democracies, yet few studies explore the linkages between the two – despite prominent arguments about voters feeling ‘left behind’. We argue that rising inequality not only intensifies relative deprivation, but also signals a potential threat of social decline, as gaps in the social hierarchy widen. Hence, voters higher up in the social hierarchy may turn to the radical right to defend existing social boundaries. Using International Social Survey Programme (ISSP) data from 14 OECD countries over three decades, we find that rising income inequality increases the likelihood of radical right support – most pronouncedly among individuals with high subjective social status and lower-middle incomes. Adding to evidence that the threat of decline, rather than actual deprivation, pushes voters towards the radical right, we highlight income inequality as the crucial factor conditioning perceived threats from a widening social hierarchy.